AMPEROMETRIC DETERMINATION OF PERRHENATE ANION USING A MICROSCOPIC INTERFACES BETWEEN TWO IMMISCIBLE ELECTROLYTE SOLUTIONS - L. Yu. Martynov; E. V. Lopatukhin; A. A. Astafyev; A. M. Shakhov; V. A. Nadtochenko; N. K. Zaitsev (Тонкие химические технологии)
Voltammetric responses associated with the simple reaction of perrhenate anions transfer across polarized micro-interfaces between two immiscible electrolyte solutions (micro-ITIES) was investigated, and their sensing applications were demonstrated. The micro-ITIES array was formed at polyethylene terephthalate membranes containing a 196 microhole array of radius 10.0±0.1 μm using a femtosecond laser. The characteristics of perrhenate ions transfer at the water/2-nitrophenyloctyl ether interface were first investigated using cyclic voltammetry (CV). CV was used in the estimation of some of the perrhenate anions thermodynamic parameters, such as the formal transfer potential and the Gibbs transfer energy. The technique of alternating current stripping voltammetry (ACSV) was also utilized to improve the sensitivity of the perrhenate anion detection. Under optimized preconcentration and detection conditions, a limit of detection of 0.3 μM with a wide linear dynamic range extending from 1.0 to 100 μM was achieved. The effect of various potential interfering anions on the perrhenate sensor was also investigated and an excellent selectivity over SCN-, I-, NO3-, NO2-, CO32-, SO42-, MoO42-, WO42- and CH3COO- ions was also achieved. This enabled quantitative measurements of rhenium in some mineral raw samples and the data was also validated by comparing with inductively coupled plasma atomic emission spectroscopy.